How to develop the creative milieu and physical resources of the university campus into a sustainable innovation zone – The case of Morasko-Poznań, Poland - Męczyński, Michał; Ciesiółka, Przemysław; WeissMarc A.; Egedy, Tamás (Hungarian Geographical Bulletin, 2025)
This article evaluates the development of the Morasko Campus of Adam Mickiewicz University (AMU) in Poznań, one of Poland’s leading academic centres, in relation to its alignment with the Sustainable Innovation Zone (SIZ) concept. This concept refers to urban districts that concentrate sustainable innovation activities within an attractive, creative milieu. The study draws on model solutions from the literature on creating city innovation districts, focusing on some physical assets considered to be sustainable innovations. The findings indicate that the Morasko Campus has begun to integrate elements of the SIZ concept, particularly in selected public spaces and university building courtyards. Initial pilot projects have been launched to incorporate sustainable innovations, such as green roofs, green walls, and solar energy photovoltaic panels, into the campus buildings. As sustainability becomes a central focus of the University’s development policy, it is anticipated that these initiatives will increase in the near future.